2021
DOI: 10.1148/rg.2021200081
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of Fetal Growth Abnormalities

Abstract: List the terminology used to describe abnormal fetal growth.Describe the roles of Doppler US and other examinations of fetal well-being in the management of growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…The IUGR is associated with adverse effects on energy metabolism [ 44 ]. Previous studies showed that piglets with IUGR had higher levels of insulin resistance and hepatic lipid accumulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IUGR is associated with adverse effects on energy metabolism [ 44 ]. Previous studies showed that piglets with IUGR had higher levels of insulin resistance and hepatic lipid accumulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…By recommendation of WHO [10][11], other more reliable parameters are included in the classification, such as head circumference (HC), biparietal diameter (BPD), femur length (FL), limbs circumference and abdominal circumference (AC). Measurements of femur length and upper leg circumference are potential parameters for assessment of fetal weight with even distribution of muscle mass and fat tissue during fetal growth and development [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, at least two ultrasound scans conducted at different intervals are necessary to track this progression (21) (22) Fetuses with an estimated fetal weight below the 10th percentile, according to the trajectory model, should undergo serial ultrasound scans every 3-4 weeks following diagnosis. This will allow the supervising clinician to periodically evaluate the fetus's viability perinatal risk and determine the appropriate timing for delivery (23). When dealing with pregnancies that have no date or have been poorly dated, accurately diagnosing the incorrect size of the fetus presents a distinct issue.…”
Section: Serial Growth Scanmentioning
confidence: 99%